Learning Strategy at The University of Muhammadiyah Gresik - Muyasaroh muyasaroh; Mohammad Ahyan Yusuf S. (TAMADDUN : Jurnal Pendidikan dan Pemikiran Keagamaan, 2016)
Basicly a lecturer should have the skills determine the learning strategy because learning strategy is important for student. For that this research aims to know learning strategy applied by a lecturer to student in the lecture. So as to formulate a problem of this research is how learning strategy by the lecturer of Islamic religion faculty at the University of Muhammadiyah Gresik. This research aimed to describe the learning strategy conducted by the lecturer of Islamic religion faculty at the University of Muhammadiyah Gresik. As for the methods used in this research is qualitative descriptive method with using data collection techniques include interviews, observation and documentation. Than the object of research in the form of the activities of learning strategy applied by the lecturer of Islamic religion faculty at the time lecture in the classroom, while the research subject is the lecturer of Islamic religion faculty and the students of Islamic religion faculty that is possible to add the necessary data in research. Data analysis using model data analysis of Milles and Hubberman with test the validity of the data using triangulation techniques and member check.